MOLOKAN RELIGIOUS COMMUNITY IN MODERN ARMENIA - Andreeva, Ulia Olegovna (History, Archeology and Ethnography of the Caucasus, 2021)
The religious group of the Russian Molokans (along with the Dukhobors and Subbotniks) was exiled from Russia to Transcaucasia in the 19th century and today constitutes an insignificant but noticeable minority in mono-ethnic Armenia. These “cultists” found themselves in an ambiguous position in Transcaucasia. On the one hand, they served the Russian Empire, on the other – they were considered heretics and enemies of the Russian statehood. The Molokan religion is neither homogenous nor a static phenomenon; it is a collective term, which can be associated with both groups and single individuals. The article is based on the author’s field material, collected during the expedition to the Molokans in Armenia in 2018-2019. The study aims to reveal how such an isolated, static, inflexible religious community deals with the challenges of the modern world in a democratic state. Strict norms, an abundance of prohibitions and isolation were well maintained in the era of persecution, but how much is it possible to preserve them in today’s Armenia? The main subject of the paper is the interaction of ethno-religious minorities with the secular world. The boundaries between the secular and the religious are conditional, and are meaningful, first of all, for the believers themselves. Today they quite easily maintain their religiosity in a society where the majority follows the national religion – the Armenian Apostolic Church. When describing themselves, the Molokans turn to enumerate prohibitions that are important today but are no longer observed with such care as before, especially among the younger generation. The main fears of the elders are related to the risks of “mixing” and losing their religious identity. Living in a foreign ethnic environment gives you more opportunities to preserve your own customs and not giving up on religion.
Keywords: Molokans; Pryguns; Transcaucasia; Armenia; religious minority; cultism; state